Pemahaman Literasi Keuangan Digital Dalam Mencegah Pinjaman Online Ilegal Pada Pengurus Ranting ‘Aisyiyah Ngasem - Amalina, Nur; Erikawati, Civi; Muhammad Roffifudin, Farid; Galuh Ani Sekar Arum, Aulia; Natalia Miyanti, Sapta (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
Financial Technology is financial technology developed for purposes in the financial sector. One type of Financial Technology is Peer-to-Peer (P2P) Lending, which is an information technology-based lending service. Technological innovation has brought a more practical financial transaction process, one of which is applied to online loans. From 2017 to 2023, as many as 7,502 illegal online lending entities were closed by the OJK. This has also led to many cases of public complaints regarding online loans, which are caused by a lack of digital financial literacy among the public. To reduce these cases, the author provides a solution that requires an increasing understanding of digital financial literacy, especially illegal online loans, in society. The aim of this Community Service (PkM) activity is to understand digital financial literacy in the community. The target of this activity is the women of the 'Aisyiyah Ngasem Branch Management, Colomadu District, Karanganyar. The method used is socialization, where the team not only delivers material but also involves a question-and-answer session with the participants. As a result of this service, out of 45 participants, 25 participants had heard the term pinjol, and 20 participants were for the first time. With this outreach, all participants know and understand what online loans are and how to avoid illegal online loans. This service activity lasts for 150 minutes, from opening to closing.  The socialization process went smoothly and received good feedback from participants, marked by the participants' high enthusiasm in asking questions about digital financial literacy and online loans.